Burden of Dental Caries in the Nepalese Children: A Literature Review - Khanal, Sanskriti; Shah, Priyanka; Ghimire, Pratikshya (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Dental caries is a biofilm mediated, sugar driven, multifactorial, dynamic disease that results in the phasic demineralization and remineralization of dental hard tissues. It is one of the most common global oral health problems that can occur throughout life, affecting both primary and permanent dentition. The only National Pathfinder survey of Nepal 2004 had shown 57.5% of 5-6 years age group and 25.6% of 12-16 years age group suffer from dental caries. Pain and discomfort due to untreated dental caries was 18% in 5–6-year-old. This review article draws attention to the current scenario of prevalence of dental caries in Nepalese children, which is needed to frame preventive strategies, policies and manpower allocations suitable for children. After identifying articles from PubMed, Google Scholar and hand searching, the prevalence of dental caries in Nepalese children is reviewed together.